COOLING LOAD ANALYSIS IN THE CENTRAL SURGERY ROOM OF SULTAN IMANUDDIN HOSPITAL PANGKALAN BUN BASED ON THE REGULATION OF THE MINISTER OF HEALTH OF THE REPUBLIC OF INDONESIA NUMBER 7/MENKES/2019 - Khusnaini, Alfan; Aspiansyah, Aspiansyah; Harianto, Agus; Handoyo, Budi; Munajat, Cecep (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2020)
In Sultan Imanuddin Hospital's central surgical room, analyzing the cooling load is essential to maintaining optimal working conditions for medical procedures. This study aimed to evaluate the efficacy of the cooling system in the surgical room according to the Republic of Indonesia's Minister of Health Regulation Number 7 of 2019. The investigation measured the cooling load required to maintain the room temperature within established health standards. The central surgical room was found to have a cooling load of 4301.462 kcal/h, equivalent to 17059.60 Btu/h. The hospital's air conditioning system, with a capacity of 2 PK or 18000 Btu/h, was determined to be sufficient to handle this load, providing a margin of 940.4 Btu/h. These findings enhance our understanding of the hospital's cooling system and offer recommendations to ensure that patients and medical personnel receive high-quality, safe care.